Relationship Between Emotional Intelligence and Communication Skills Among High School Students in Hamadan Based on the Theory of Social Support - Narges Nouri; Babak Moeini*; Akram Karimi-Shahanjarini; Javad Faradmal; Ali Ghaleiha; Maryam Asnaashari (Hamadan University of Medical Sciences, 2014)
Background and Objectives: There has been growing interest in adolescents' emotional intelligence and strengthening their various skills including effective and efficient communication. Therefore, this study sought to investigate the relationship between emotional intelligence and communication skills of high school students in Hamadan, Iran based on the theory of social support. Materials and Methods: This descriptive-analytical study was conducted in 2014. Multistage sampling was performed to select 497 students from high schools of Hamadan. The subjects completed a questionnaire containing items on communication skills, emotional intelligence, and social support. The collected data were analyzed using Pearson's correlation test, Spearman's correlation test, t-test, and analysis of variance in SPSS-18. Results: There was a significant relationship between emotional intelligence and communication skills of the participants. The students had a moderate level of communication skills. In general, girls enjoyed higher levels of communication skills, emotional intelligence, and social support (except appraisal support) compared to boys. Moreover, constructs of social support were significantly related with emotional intelligence and communication skills. Conclusion: According to our findings, educational interventions and training packages for students, parents, and schoolteachers are required to improve the students' emotional intelligence and communication skills.